2012
DOI: 10.7567/jjap.52.018001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pad Surface Micro-Texture on Removal Rate during Interlayer Dielectric Chemical Mechanical Planarization Process

Abstract: The effect of pad surface micro-texture on removal rate in interlayer dielectric chemical mechanical planarization was investigated. Blanket 200mm oxide wafers were polished on a Dow â IC1000ä K-groove pad conditioned at two different conditioning forces. The coefficient of friction increased slightly (by 7%) while removal rate increased dramatically (by 65%) when conditioning force was increased from 26.7 to 44.5 N. Pad surface micro-texture analysis results showed that pad surface contact area decreased dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…(6) Separately, Liao et al found that a pad conditioned at a higher downforce resulted in a higher oxide removal rate due to a dramatic decrease in pad surface contact area, therefore an increase in local contact pressure. (11) These studies provide evidence that the magnitude of conditioning downforce can cause different outcomes to the pad surface microtexture. As such, there is a need to further investigate the relationship between conditioning downforce and its effect on the micro-texture during oxide CMP.…”
Section: Introductionmentioning
confidence: 92%
“…(6) Separately, Liao et al found that a pad conditioned at a higher downforce resulted in a higher oxide removal rate due to a dramatic decrease in pad surface contact area, therefore an increase in local contact pressure. (11) These studies provide evidence that the magnitude of conditioning downforce can cause different outcomes to the pad surface microtexture. As such, there is a need to further investigate the relationship between conditioning downforce and its effect on the micro-texture during oxide CMP.…”
Section: Introductionmentioning
confidence: 92%
“…Since shear force is a result of mechanical interactions among the pad, the abrasive particles and the wafer, a higher average shear force should result in a higher mean removal rate for a nonchemically limited CMP process such as ILD CMP. Liao et al [12] correlated the ILD removal rate with shear force and characterized pad surface micro-texture by using laser confocal microscopy. Her investigation shows the feasibility of an on-line and non-destructive shear force detection method for determining the pad surface micro-texture during oxide CMP.…”
Section: Resultsmentioning
confidence: 99%
“…CMP typically refers to chemical mechanical planarization. As its name indicates, CMP simultaneously employs both chemical and mechanical actions to selectively remove the exposed material from elevated features for improved planarization [6][7][8][9][10][11][12][13][14]. Driven with the planarization challenge in IC manufacturing for smaller minimum feature size and more wiring levels, CMP was invented by International Business Machines (IBM) in the mid-1980s [15].…”
Section: What Is Cmp?mentioning
confidence: 99%